2011
DOI: 10.1007/s10526-011-9371-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the interaction between the exotic invasive aquatic macrophyte Myriophyllum spicatum and the native biocontrol agent Euhrychiopsis lecontei to improve augmented management programs

Abstract: Mathematical modeling is used to investigate control of the invasive aquatic plant Myriophyllum spicatum L. by the native watermilfoil weevil Euhrychiopsis lecontei Dietz. An age-structured population model with discrete development class is used to separate the destructive activity of Euhrychiopsis lecontei Dietz larvae from the relatively benign activity of the other developmental stages. Empirical model behavior is evaluated and agrees with expected system characteristics. Simulation results demonstrate dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Terrestrial plants (dicots, monocots, and nonangiosperms combined), mammals, and birds were the most modeled taxonomic groups, followed by fish, aquatic invertebrates, and terrestrial invertebrates. There were relatively few models of amphibians and reptiles and only 2 models of aquatic plants (Figure A).…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…Terrestrial plants (dicots, monocots, and nonangiosperms combined), mammals, and birds were the most modeled taxonomic groups, followed by fish, aquatic invertebrates, and terrestrial invertebrates. There were relatively few models of amphibians and reptiles and only 2 models of aquatic plants (Figure A).…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…These authors attribute wave shelter, higher temperature, predation refuge (but not light), are likely contributing factors to weevil success in smaller lakes. In addition, the modeling work by Miller et al (Miller et al, 2011) has shown diminishing returns between single‐season stockings of weevils and EWM control efficacy. That is, past 50 weevils added per season, the reduction in biomass as described by the models simulated biomass peak at the end of season is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mathematical models of aquatic macrophyte growth have been developed to study both seasonal (Herb & Stefan, 2003; Miller et al, 2011) and yearly plant growth (Best et al, 2001). These predictive models are mechanistic in nature, taking into account how macrophytes are dependent on lake characteristics such as water clarity, available nutrients, water temperature, as well as the metabolic properties of the plant itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy uptake and expenditure can be modeled as a function of age‐specific or stage‐specific body mass or age. Energy therefore drives the development of each class (Miller et al 2011; Pachzelt et al 2013). Other studies link more complicated energy budget models, such as DEB theory, to structured model parameters (Klanjscek et al 2006; Klok et al 2007).…”
Section: Key Features To Consider In Model Development and Evaluationmentioning
confidence: 99%